2020
DOI: 10.1111/jocn.15490
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing screening practice patterns for nurses in the cardiac surgery intensive care unit

Abstract: This article has been contributed to by US Government employees and their work is in the public domain in the USA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The three currently available PED screens all focus on aspiration and utilize a 3-oz water swallowing test [ 7 ], whereas growing data suggest that not all nurses are confident in performing these screens, correctly identifying signs of aspiration (i.e., wet voice). One recent study revealed that 81% of nurses working in the cardiac ICU reported having no formal training in swallow screening [ 12 ]. Nearly half, 48%, of ICU nurses reported feeling “somewhat” or “not” confident in performing screens [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The three currently available PED screens all focus on aspiration and utilize a 3-oz water swallowing test [ 7 ], whereas growing data suggest that not all nurses are confident in performing these screens, correctly identifying signs of aspiration (i.e., wet voice). One recent study revealed that 81% of nurses working in the cardiac ICU reported having no formal training in swallow screening [ 12 ]. Nearly half, 48%, of ICU nurses reported feeling “somewhat” or “not” confident in performing screens [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…One recent study revealed that 81% of nurses working in the cardiac ICU reported having no formal training in swallow screening [ 12 ]. Nearly half, 48%, of ICU nurses reported feeling “somewhat” or “not” confident in performing screens [ 12 ]. Our two-item swallowing screen provides important alternatives.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the reference book of osteopathic medicine, an example is given of altered systemic reflexes following surgery, which can be felt through palpation of the spinal musculature showing rigid muscles and the limitation of vertebral movement [2]. After an event, surgery, for example, in the cardiovascular field, patients present with problems in lingual function, with the presence of dysphagia [68,69]. Surgery to remove tumor masses from the neck or head generally favors the onset of dysphagia [70].…”
Section: The Neurological Model and The Tonguementioning
confidence: 99%